Dying to be seen : suicide and the Chinese in colonial Singapore, 1860s - 1930s - Gan, Zhen Yin (Nanyang Technological University, 2022)
This thesis offers another perspective on how suicides were regarded differently amongst the Chinese during colonial Singapore and how it interfered with the management of biological life that British colonial authority had to practice as the crown colony thrived. By using newspaper archives to analyse how the suicides were reported in the colonial press, this thesis will argue that between the 1860s to 1930s, the strategies employed to manage suicides by colonial authority were effective for European colonial subjects but not for Chinese colonial subjects. The cause for this lies in the different ‘truths’ in relation to suicide that these colonial subjects were informed by. For European colonial subjects, suicide was regarded as a tragedy and/or consequence for the pathologically ill while the Chinese colonial subject viewed it as an alternative or last resort to transform themselves into subjects of value that was advocated by Confucian thought. Therefore, colonial authority attempts to reform Chinese colonial subject into rational and non-suicidal subjects within colonial Singapore were often ineffective even with the criminalisation of suicides and the establishment of medicalise spaces to reform the Chinese. This thesis will also reveal how suicide was racialised by the colonial press in colonial Singapore.